Preparation of Financial Statements Based on SAK EMKM In Small Micro Enterprises And Menengah (MSMEs) Fostered By The Department of Agriculture, Marine Affairs and Parepare City Fishery - Sri Rezky Handayani; Arfianty Arfianty; Yadi Arodhiskara (Economos : Jurnal Ekonomi dan Bisnis, 2022)
MSMEs are economic activities that play an important role in economic growth, maka if the MSME sector is disturbed then the national economy is also disturbed, As for the purpose ofthe study is 1). To find out the process of preparing financial reports for small and medium enterprises based on SAK EMKM on MSMEs "Coastal Tavern Group" Assisted by the Parepare City PKP Office. This research uses a qualitative type of research with a descriptive approach. The descriptive qualitative research used in this study is to describe and describe the Preparation of Financial Statements for Micro, Small and Medium Enterprises (MSMEs) based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in MSMEs "Coastal Tavern Groups" Assisted by the Parepare City PKP Office. The results of the study are 1). UMKM Kedai Pesisir Group does not have real or good financial recording reports because both employees and business owners do not understand about recording financial statements based on applicable Financial Accounting Standards, 2). UMKM Kedai Pesisir Group is known that the employees taken are housewives who do not have a job and do not understand about recording, lack of knowledge of the owner of the Coastal Tavern Group MSME regarding accounting standards in the preparation of financial statements. 3). MSME activities still focus on other activities as well as production and sales only, so the time to make financial reports is still very lacking.